Factors Affecting Reversal of Plant-Based Meat Consumption : An Empirical Analysis - Gadkari, Kunal; Dhote, Tripti (Indian Journal of Marketing, 2025)
Purpose : This study showed how sustainable marketing, sensory perceptions, and consumer switching from plant-based to animal-based foods interacted. It examined how sustainable marketing and sensory impressions mediated psychological factors—desire, dissonance, and disillusion—on dietary choices and their impact on sustainable food practices. Design/Methodology/Approach : The study analyzed 185 random samples over two months using partial least squares structural equation modeling (PLS-SEM). Findings : PLS-SEM showed that sensory perceptions and sustainable marketing significantly moderated psychological variables’ effect on dietary reversal. Positive sensory experiences helped plant-based diets stick since sensory impressions significantly inhibit reversion. Sustainable marketing improved sensory impressions but reduced dietary reversals. These findings showed that sensory and marketing methods were essential for dietary impact. Limitations/Implications : Future research could examine digital marketing strategies’ qualitative and long-term effects on sustainable dietary preferences across diverse cultural contexts to improve global understanding and industry application. Practical Implications : This study helped marketers and policymakers develop methods that used sensory appeal and sustainability claims to switch consumers to more sustainable diets. Originality/Value : The research provided a framework for focused marketing techniques that encouraged plant-based diets and improved consumer behavior in sustainable food consumption.